Does Islamic Financial Inclusion Promote Economic Growth? Evidence From Oic Countries - Yasmin (PT. Samudra Solusi Profesional, 2026)
This study examines the relationship between Islamic financial inclusion and economic growth in Organization of Islamic Cooperation (OIC) countries using panel data analysis. Despite the rapid global expansion of Islamic finance, with assets exceeding 3.5 trillion, empirical evidence on its growth effects remains limited and inconclusive. This study addresses that gap by analyzing the impact of Islamic banking development, proxied by the average total assets of Islamic banks, on GDP per capita across OIC member states. Using a fixed effects estimation approach, we control for key macroeconomic determinants of growth, including conventional financial depth, trade openness, human capital, institutional quality, foreign direct investment, and inflation. The Hausman test confirms the appropriateness of the fixed effects specification, while clustered standard errors are employed to correct for heteroskedasticity and serial correlation. The results indicate that Islamic financial inclusion has a positive and statistically significant effect on economic growth. Specifically, a 1% increase in Islamic banking assets is associated with a 0.090% increase in GDP per capita. This finding suggests that Shariah-compliant financial services contribute meaningfully to economic development and operate as a complement rather than a substitute for conventional financial systems. Furthermore, institutional quality and private-sector credit are significant growth determinants, underscoring the importance of strong governance and well-developed financial systems. These findings imply that OIC countries can enhance economic performance by expanding Islamic banking infrastructure, strengthening regulatory frameworks, and improving institutional quality while maintaining balanced and inclusive financial ecosystems.